“Gastronomy in Madrid and Lima” : Realization of a live television show through a COIL experience - Alcudia Borreguero, Mario; Cervera Barriga, Esther; Gómez-Calcerrada, Manuel Albacete (Street Art & Urban Creativity, 2025)
This research is based on the experience of practical learning and teaching innovation, COIL, Collaborative Online International Learning, of the subjects 'Audiovisual Journalism' and 'Realization' of the Faculty of Humanities and Communication Sciences of the CEU San Pablo University together with the ULIMA University, in Peru. It is the development and live broadcast of a television magazine. It includes reports and interviews about the main restaurants and traditional food in the cities of Lima and Madrid offer to their visitors. In addition, some of the audiovisual creations resulting from the mobile coverage referring to the gastronomy of Madrid, in real time, made through Instagram, are disseminated.